Rational Contractions in b-Metric Spaces - Isufati, Arben (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper, we prove fixed point theorems for contractions and generalized weak contractions satisfying rational expressions in complete b-metric spaces. Our results generalize several well-known comparable results in the literature.